Efficacy of repetitive transcranial magnetic stimulation on chronic migraine: A meta-analysis - Zhong, Jiugen; Lan, Wanting; Feng, Yanqing; Yu, Ligen; Xiao, Rang; Shen, Yingying; Zou, Zhi; Hou, Xiaohui (Frontiers in Neurology, 2022)
Introduction Migraine is a neurovascular disorder that affects the quality of life of more than 1 billion people worldwide. Repetitive transcranial magnetic stimulation (rTMS) is a neuromodulation tool that uses pulsed magnetic fields to modulate the cerebral cortex. This meta-analysis ascertained the therapeutic or preventive effect of rTMS on chronic migraine. Methods We performed a database search of PubMed, Web of Science, Embase, and the Cochrane Library from January 2004 to December 2021. Eligible studies included randomized controlled studies of the analgesic effects of rTMS in patients with chronic migraine. Results Eight studies were included. Random effects analysis showed an effect size of −1.13 [95% confidence interval (CI): −1.69 to −0.58] on the frequency of migraine attacks, indicating that rTMS was more effective for decreasing migraine attacks than the sham rTMS. Conclusions The meta-analysis revealed that rTMS is an effective approach for reducing migraine attack when the dorsolateral prefrontal cortex was stimulated. However, rTMS may not be suggested as a method to reduce the pain level. Systematic review registration http://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42021228344.